2006
DOI: 10.1103/physrevb.74.195301
|View full text |Cite
|
Sign up to set email alerts
|

Theory of electron spin decoherence by interacting nuclear spins in a quantum dot

Abstract: We present a quantum solution to the electron spin decoherence by a nuclear pair-correlation method for the electron-nuclear spin dynamics under a strong magnetic field and a temperature high for the nuclear spins but low for the electron. The theory incorporates the hyperfine interaction, the intrinsic (both direct and indirect) nuclear interactions, and the extrinsic nuclear coupling mediated by the hyperfine interaction with the single electron in question. The last is shown to be important in free-inductio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
553
4
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 306 publications
(588 citation statements)
references
References 41 publications
(84 reference statements)
26
553
4
5
Order By: Relevance
“…[31] Yao et al derive a similar quasiparticle picture via direct calculation of the time dependent correlation function for the electron spin. However, the authors did not calculate the quasiparticle relaxation times.…”
Section: Mean Field Theory Of Noise Broadening: Quasiparticle Lifetimesmentioning
confidence: 99%
See 3 more Smart Citations
“…[31] Yao et al derive a similar quasiparticle picture via direct calculation of the time dependent correlation function for the electron spin. However, the authors did not calculate the quasiparticle relaxation times.…”
Section: Mean Field Theory Of Noise Broadening: Quasiparticle Lifetimesmentioning
confidence: 99%
“…Recently, it was shown that the electron mediated inter-nuclear coupling [Eq. (70)] may be exploited in order to recover electron spin coherence lost for the nuclear spin bath [42]. We will certainly see many other interesting developments in the near future.…”
Section: Conclusion and Outlook For The Futurementioning
confidence: 99%
See 2 more Smart Citations
“…These short operation times together with the demonstrated coherence times of a few microseconds 7 and predicted coherence times of up to 100 microseconds [27][28][29] suggest that the requirements for quantum error correction of two-electron spin qubits are within reach. Furthermore, our ability to record the magnetic field gradient opens the way towards feedback control of the nuclear environment that would prolong T * 2 and thereby reduce the number of error correcting pulses needed.…”
mentioning
confidence: 99%